Modelagem urbana e regional com autômatos celulares e agentes: Panorama teórico, aplicaç\~oes e política públia - Bernardo Alves Furtado; Hedwig van Delden (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The objective of this paper is to review the richness of regional and urban modeling literature and case studies with an emphasis on cellular automata. It aims at demonstrating its usefulness for real public policy use. This work is aimed at those with a practical approach at public policies who wish to have more scientific basis. In order to achieve this hands-on approach basic definitions are posed followed by a discussion of advantages and criticisms. A public policy focus in Brazil closes the paper.
Keywords: R1; H7; 330